A High Performance Massively Parallel Approach for Real Time Deformable Body Physics Simulation - Farias, Thiago S. M. C. de; Almeida, Mozart W. S.; Teixeira, João Marcelo X. N.; Teichrieb, Veronica; Kelner, Judith (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2008: Anais do XX International Symposium on Computer Architecture and High Performance Computing, 2008)
Single processor technology has been evolving across last decades, but due to physical limitations of chip manufacturing process, the industry is pursuing alternatives to sustain computational power growth,including the creation of multi-core systems. Parallel computing targets problems that are scalable and possibly distributed, dividing the problem into smaller pieces. This approach may be explored to satisfy real-time constraints required by real time physics simulation. This work introduces an optimal solution to implement accurate simulation of deformable bodies in real time. This is accomplished through the use of a meshless simulation technique, known as Point Based Animation, implemented using a parallel framework:the NVIDIA Compute Unified Device Architecture(CUDA). Our implementation showed significative improvements on performance in comparison to the former CPU one: impressive speedups around 20times could be achieved in the simulation of deformable bodies with 575 physical elements (phyxels) and53,504 surface elements (surfels).